Erratum to: Genome Characteristics of Lactobacillus fermentum Strain JDFM216 for Application as Probiotic Bacteria - Chang, Sung Yong; Heo, Jaeyoung; Park, Mi Ri; Song, Min-Ho; Kim, Jong Nam; Jo, Sung Ho; Jeong, Do-Youn; Lee, Hak Kyo; Kim, Younghoon; Oh, Sangnam (Journal of microbiology and biotechnology, 2017)
This erratum is being published to correct the 1st author's name of above manuscript by Jang et al. that was published in Journal of Microbiology and Biotechnology (2017, 27: 1266-1271). The 1st author name(Sung Yong Jang) should appear as 'Sung Yong Chang'.